Modeling and Simulation for Electric Vehicle Applications - Amine Fakhfakh, Mohamed (IntechOpen, 2016)
The book presents interesting topics from the area of modeling and simulation of electric vehicles application. The results presented by the authors of the book chapters are very interesting and inspiring. The book will familiarize the readers with the solutions and enable the readers to enlarge them by their own research. It will be useful for students of Electrical Engineering; it helps them solve practical problems.